Results of Type I Tympanoplasty Using Fascia with or without Cartilage Reinforcement: 10 Years’ Experience - Kouhi, Ali (Iran J Otorhinolaryngol, 2018)
INTRODUCTION: There remains controversy about the optimal kind of graft to repair tympanic membrane. The purpose of this study was to evaluate the anatomical and auditory outcomes of type I tympanoplasty using fascia with or without cartilage reinforcement. MATERIALS AND METHODS: This retrospective cohort study was conducted from 2005 to 2015. All cases were surgically treated by a single surgeon. We excluded cases in which the etiology of chronic otitis media was cholesteatoma. According to the use of cartilage reinforcement in the posterosuperior part of the graft, patients were divided into two groups, and the results of anatomical and auditory evaluation were compared between the two groups. The anatomical outcome was grafting success and the auditory outcome was improvement of air bone gap (ABG). RESULTS: A total of 320 patients were classified in Group A (tympanoplasty with fascia temporalis only) and 346 were in Group B (tympanoplasty with cartilage reinforcement). All patients were followed for at least 2 years. The overall success rate in the two groups was 91.6% and 93.4%, respectively (P=0.3). The most common cause of failure in the two groups was re-perforation (5.6% and 3.8%, respectively). The improvement of ABG in two groups was 18.5 dB and 3.2 dB, respectively. The difference between two groups was statistically significant (P<0.001). CONCLUSION: In patients with dry perforation of the tympanic membrane, the anatomical success with tympanoplasty with fascia only or with cartilage reinforcement was similar. However, hearing improvement in the fascia only group was greater than in the group undergoing cartilage reinforcement.